RANCANG BANGUN SISTEM PEMUTUS ARUS SEBAGAI PENGAMAN TEMPERATUR BERLEBIH PADA INKUBATOR BAYI - Indah Nursyamsi Handayani; Wike Kristianti; Mamurotun Mamurotun; Andy Sambiono (Poltekkes Kemenkes Padang, 2021)
Several countries in the world, including Indonesia, have reported baby-care accidents in the baby incubator due to the failure of the temperature control system to maintain a stable temperature. Therefore, this study reports the design of an circuit breaker system as an over-temperature safety in a baby incubator. Experimentally, the prototype consists of hardware design, software design, and testing system design. The hardware design has four main part, sensing layer using PT1000 as a temperature sensor, data processing layer using an ESP32 microcontroller, a circuit breaker system using a solid-state relay as an electronic switching, and LCD as a display. System testing has been done by evaluating the temperature readings on a prototype against the HTC-02 digital thermometer instrument and carried out in the electromedical engineering laboratory. The results show the accuracy of the temperature parameter is 99% and the circuit breaker system is able to cut the current from the power supply to the appliance when the temperature is more than 39°C which is indicated by an incandescent lamp